2021
DOI: 10.1093/eurjpc/zwaa162
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response effects of physical activity on all-cause mortality and major cardiorenal outcomes in chronic kidney disease

Abstract: Aims Physical activity has a protective effect against mortality and cardiovascular events in chronic kidney disease (CKD) patients. Nonetheless, how different levels of physical activity affect the health benefits in CKD remains unclear. This study aimed to investigate the dose–response effects of physical activity on mortality and major cardiorenal events in CKD. Methods and results We evaluated a longitudinal cohort of 450… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
0
21
0
1
Order By: Relevance
“…Peritoneal dialysis was first translated into Chinese in 1960 and did not enter the Chinese market until the late 1990s [ 14 , 15 ]. In many countries, the prognosis of PD patients is equal to or better than that of HD [ 16 , 17 ]. Based on this, this study focused on the effect of peritoneal dialysis compared with hemodialysis on renal function and quality of life in patients with end-stage renal disease to provide evidence-based medicine for patients with end-stage renal disease to choose peritoneal dialysis or hemodialysis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Peritoneal dialysis was first translated into Chinese in 1960 and did not enter the Chinese market until the late 1990s [ 14 , 15 ]. In many countries, the prognosis of PD patients is equal to or better than that of HD [ 16 , 17 ]. Based on this, this study focused on the effect of peritoneal dialysis compared with hemodialysis on renal function and quality of life in patients with end-stage renal disease to provide evidence-based medicine for patients with end-stage renal disease to choose peritoneal dialysis or hemodialysis treatment.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cohort study found that 7.5–15 metabolic equivalent hours per week (MET-h/week) was associated with the lowest risk of cardiovascular events. 58 Regrettably, the benefit of exercise on cardiovascular risk factors cannot be determined because there are an insufficient number of conclusive studies that assess exercise effects on overall cardiovascular health. In a systematic review by Heiwe et al , a meta-analysis including two trials found that exercise improved cardiovascular function in patients with CKD, as reflected in the SD of all normal RR intervals and left ventricular mass index.…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose effects of exercise in the context of the cardiovascular health of patients with CKD should be considered. A recent cohort study found that 7.5–15 metabolic equivalent hours per week (MET-h/week) was associated with the lowest risk of cardiovascular events 58. Regrettably, the benefit of exercise on cardiovascular risk factors cannot be determined because there are an insufficient number of conclusive studies that assess exercise effects on overall cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%
“…Variables previously shown to be associated with CKD and mortality were included as covariates [ 16 , 17 , 18 ]. The demographic and health-related information was collected by standardized questionnaires.…”
Section: Methodsmentioning
confidence: 99%